Planejamento urbano da bacia do córrego Samambaia (Goiânia-GO) utilizando o SWMM - Storm Water Management Model - Rocha, Nayda (2013)
The effect of urbanization and insufficient supervision of the use of natural resources by the government has led to increasing degradation of the environment in Brazil. This can be seen by the suppression of riparian vegetation, which is essential for the survival and maintenance of the quality of water sources. In this sense, the actions of development of land, housing provision and sanitation in Brazil must have, among other objectives, to ensure an environment conducive to ecosystems and human life support. This research aimed to identify the characteristics of occupation of Córrego Samambaia Basin in Goiânia, used for public water supply, correlating land use with hydrological processes. The methodology adopted consisted in: identifying the theoretical framework from literature and choose a basin to develop a case study; select and gather information from the object of study contained in published documents, restricted texts, satellite imagery, site visits, to generate the necessary data for modeling, and apply the hydrologic model Storm Water Management Model (SWMM) in three distinct periods and three proposed scenarios to understand the hydrological responses in the study area due to different levels of human occupation. The results obtained with this research indicate that the hydrological watershed responses can vary widely if the waterproofing process continue to increase. Results shown that between 1992 (with impervious area of 7%) and the proposed Scenario 3 (with impervious area of 70%) the increase in runoff is approximately 24 times while the infiltration becomes 70% smaller. If the basin achieves an index greater than 50% of impervious area, it will probably become unviable for public supply purposes. In order to preserve the watershed for its main purpose to continue supplying the municipality this study proposes an appropriated urban planning, with the construction of a Linear Park along the creek and the adoption of new levels of urban occupation. This planning model may be used in other urban basins, taking into account the characteristics of each site.